Readiness of apartment building residents for hot water supply modernization in Ukraine - Кудінов, Ігор Олексійович; Kudinov, Ihor O.; Кудінов, І. О.; Kudinov, I. О.; Serheieva, K. М.; Сергеєва, К. М.; Клименко, А. О.; Klymenko, A. О. (Одеса, 2022)
Features of social and institutional readiness of residents of apartment buildings (condominiums) for reforms of centralized hot water supply in Ukraine are analyzed. The paper represents results of social survey research of residents of apartment buildings in Zaporizhzhia (Ukraine). The methodological basis of the research is generally scientific and special sociological methods of scientific cognition. The research determines socio-demographic and institutional characteristics of centralized hot water supply services consumers in Zaporizhzhia, the level of interest in the preservation and modernization of centralized hot water supply system in the city, the level of readiness of apartment building residents for collective responsibility for the consumption of hot water supply services and strategies for modernization of the centralized hot water supply system. Research results identified possible ways to increase apartment building residents’ readiness for modernization: 1) development of the subjectivity of the apartment building residents, because it is impossible to solve common problems of such buildings in case of unity absence of their inhabitants; 2) increasing the level of social interaction between the community and local authorities; 3) develop institute of social organizers (social technicians). Research results suggest that condominium residents of Zaporizhzhia show a very low level of awareness in the field of housing legislation and the condition of their own buildings and the fact that every such resident understands the feasibility and need to modernize the existing hot water supply system. The main obstacle to the modernization of hot water supply systems is the need to attract large financial resources. The second – is the unwillingness of apartment building residents to cooperate. One of the ways to solve the problem is to provide a quality information campaign to raise public awareness of: financial capabilities for apartment buildings; better practices of project activities of OSBB buildings.

Проаналізовано особливості соціальної та інституційної готовності мешканців багатоквартирних будинків до реформ централізованого гарячого водопостачання в Україні. У статті представлені результати соціального опитування мешканців багатоквартирних будинків м. Запоріжжя (Україна). Методологічну основу дослідження складають загалом наукові та спеціально-соціологічні методи наукового пізнання. Дослідженням визначено соціально-демографічні та інституційні характеристики споживачів послуги централізованого гарячого водопостачання міста Запоріжжя, рівень зацікавленості у збереженні та модернізації системи централізованого гарячого водопостачання міста, рівень готовності мешканців багатоквартирного будинку до колективної відповідальності. на споживання послуг гарячого водопостачання та стратегії модернізації системи централізованого гарячого водопостачання. Результати дослідження визначили можливі шляхи підвищення готовності мешканців багатоквартирних будинків до модернізації: 1) розвиток суб’єктності багатоквартирних будинків, оскільки неможливо вирішити загальні проблеми таких будинків у разі відсутності єдності їх мешканців; 2) підвищення рівня соціальної взаємодії громади та місцевої влади; 3) розвивати інститут соціальних організаторів (соціальних технологів). Результати досліджень свідчать про те, що мешканці багатоквартирних будинків міста Запоріжжя демонструють дуже низький рівень обізнаності у сфері житлового законодавства та стану власної забудови та той факт, що кожен такий мешканець розуміє доцільність та необхідність модернізації існуючої системи гарячого водопостачання. Основною перешкодою на шляху модернізації систем гарячого водопостачання є необхідність залучення великих фінансових ресурсів. Друга перешкода – небажання мешканців багатоквартирних будинків співпрацювати. Одним із шляхів вирішення проблеми є проведення якісної інформаційної кампанії для підвищення обізнаності населення щодо фінансових можливостей багатоквартирних будинків та кращих практик проектної діяльності на рівні багатоквартирних будинків.
Kudinov I. О. Readiness of apartment building residents for hot water supply modernization in Ukraine / I. О. Kudinov., K. М. Serheieva, A. О. Klymenko // Актуальні проблеми філософії та соціології : Науково-практичний журнал / Голов. ред. С. Г. Секундант, відпов. ред. Д. В. Яковлев ; Міністерство освіти і науки України ; Національний університет "Одеська юридична академія". - Одеса, 2022. - Вип. 34. - С. 37-46.
Keywords: entralized hot water supply; modernization; apartment building; social planning; actor; social organizer; централізоване гаряче водопостачання; модернізація; багатоквартирний будинок; соціальне планування; суб’єкт; соціальний технолог; Research Subject Categories::SOCIAL SCIENCES; Research Subject Categories::LAW/JURISPRUDENCE